Optimizing the distal anchorage in stabilization for the traumatic adjacent lumbar vertebra fracture in an adolescent idiopathic scoliosis patient who had posterior spinal fusion: a novel surgical technique - Sze Khiong Fam; Chee Kidd Chiu; Chris Yin Wei Chan; Mun Keong Kwan (Acta Orthopaedica et Traumatologica Turcica)
The incidence of traumatic spine fractures (TSF) is increasing worldwide, with a reported annual incidence of up to 32.8 per 100000 persons. However, there are only a few cases of spine fractures reported in adolescent idiopathic scoliosis (AIS) patients after posterior spinal fusion (PSF) in the literature. Fractures adjacent to fusion blocks that extend into the lower lumbar spine pose a unique challenge as stabilization of such fractures might require an extension of instrumentation to L5 or the pelvis. We report a novel surgical technique where bilateral pedicle and cortical screws at L4 and supplementary rods that connect the cortical screws to the main rods via dominos were implemented for optimizing the distal anchorage for TSF stabilization following an L3 Chance fracture in an AIS patient who had undergone T4-L2 posterior spinal fusion.